Association of prehospital invasive blood pressure measurement and treatment times of intubated patients with suspected stroke – a retrospective study - Michael Eichlseder; Nikolaus Schreiber; Alexander Pichler; Michael Eichinger; Sebastian Labenbacher; Barbara Hallmann; Simon Orlob; Paul Zajic; Simon Fandler-Höfler (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Invasive blood pressure measurement is commonly used in in-hospital patients with stroke requiring general anesthesia, but is much less established in the prehospital setting. While it allows for more precise blood pressure management, it might also lead to prehospital treatment delays. Therefore, this study aims to evaluate the potential impact of prehospital invasive blood pressure measurement on treatment times. Methods Adult patients (≥ 18 years) with suspected stroke (both ischemic and hemorrhagic) and prehospital induction of emergency anesthesia by physicians admitted to the University Hospital of Graz between January 1st, 2018 and December 31st, 2023, were included. Optimal one-to-one matching using a propensity score for prehospital invasive blood pressure measurement based on patient age, patient sex, treatment by helicopter emergency medical services and Glasgow coma scale on scene was performed. Primary outcome was the time-interval between on-scene arrival of the prehospital physician and first cranial computed tomography (CCT). Results One hundred patients with suspected stroke and prehospital emergency anesthesia were identified, of whom 67 (67%) had prehospital invasive blood pressure measurement. After matching, 33 patients of each cohort were used for main analysis. Median (25th to 75th percentile) time between on-scene arrival and first CCT was 79 (70–87) minutes in the prehospital measurement group, compared to 73 (67–81) minutes in the group with in-hospital initiation of invasive measurement (p = 0.21). On-scene time was longer in the prehospital group [45 (37–51) vs. 36 (33–43) minutes, p = 0.009], while transport duration [18 (11–25) vs. 20 (13–31) minutes, p = 0.20] and time spent in the resuscitation room [16 (12–20) vs. 16 (12–21) minutes, p = 0.391] did not differ. Conclusion In summary, among patients with suspected stroke who underwent prehospital intubation, time from on-scene arrival to the first CCT was not prolonged in those who received prehospital invasive blood pressure measurement compared to those who received it in-hospital.